The scientists of the IVIC in the evolution of science and technology policy during the Chávez administration in Venezuela. Issue 1 (1st January 2019) - Laya, Damny; Vessuri, Hebe
ABSTRACT: Hugo Chávez's assumption of the presidency in late 1999 brought about major institutional change in Venezuela, and in its science and technology. Some authors speak of a breakage of the scientific community's "social contract" with the state through the inroads of a new political bias or politicization, and of a replacement of decision-making among the scientific community traditionally responsible for the direction of science and technology policy (STP) – in which the scientific community of the Venezuelan Institute of Scientific Research (IVIC) had been a historically influential, not to say dominant, actor – by other actors of Venezuelan society. This study aims to elucidate the changes occurring in the Chávez administration's STP and, especially, in the role played by one of its actors – the scientific community of the IVIC – while identifying the political actions of the key actors responsible for that policy and highlighting the power they wielded, gained, or lost over its development.